Kinetic Mechanism of Human Histone Acetyltransferase P/CAF - Tanner, Kirk G; Langer, Michael R; Denu, John M (Biochemistry (Easton), 2000)
Human transcriptional coactivator P/CAF (p300/CBP-associating factor) is a histone acetyltransferase (HAT) and is a member of the GNAT (GCN5 related N-acetyltransferases) superfamily. P/CAF was originally identified by its ability to activate transcription of a variety of genes through its interaction with p300/CBP. Though Lys-14 of histone H3 appears to be the preferred substrate, other nonhistone proteins can also serve as substrates for P/CAF. However, few studies have addressed the catalytic and kinetic mechanisms of histone/protein acetylation by P/CAF. In this study, we have systematically determined the kinetic mechanism for P/CAF, identified the critical ionizations for binding/catalysis, and established the rate-limiting step in turnover. This was accomplished by a variety of approaches including pH-dependent activity measurements, Bi-substrate kinetic analysis, authentic product inhibition by coenzyme A (CoA) and acetylated H3 (Ac-Lys-14) peptide, direct measurements of substrate/product binding affinities (equilibrium dialysis), and a pre-steady-state quench-flow analysis. The results are consistent with a fully ordered Bi-Bi kinetic mechanism, where chemical catalysis is rate-determining. Acetyl-CoA (AcCoA) binds with high affinity (K d = 0.64 ± 0.12 μM) to the free form of the enzyme. Histone H3 peptide binds (apparent K d = 116 ± 17 μM) only after AcCoA is bound. No H3 peptide binding to the free enzyme was detectable. In the ternary complex, the ε-amino of Lys-14 (H3 peptide substrate) directly attacks the carbonyl carbon of AcCoA, transferring the acetyl group to the acceptor peptide substrate (rate-limiting step). Products are released in an ordered fashion, with Ac-Lys-14 H3 released first followed by release of CoA. The pH dependency of the k cat/K m parameter revealed two P/CAF ionizable groups (pK a values of 6.9 and 7.5) that must be unprotonated for activity. The group with a pK a value 7.5 was assigned to Glu-570, which is the proposed general base catalyst, abstracting a proton from the ε-amino group and facilitating nucleophilic attack.